Understanding Physiology in the Continuum: Integration of Information from Multiple -Omics Levels - Kamisoglu, Kubra; Acevedo, Alison; Almon, Richard R.; Coyle, Susette; Corbett, Siobhan; Dubois, Debra C.; Nguyen, Tung T.; Jusko, William J.; Androulakis, Ioannis P. (Frontiers in Pharmacology, 2017)
In this paper we discuss approaches for integrating biological information reflecting diverse physiologic levels. In particular we explore statistical and model-based methods for integrating transcriptomic, proteomic and metabolomics data. Our case studies reflect responses to a systemic inflammatory stimulus and in response to an anti-inflammatory treatment. Our paper serves partly as a review of existing methods and partly as a means to demonstrate, using case studies related to human endotoxemia and response to methylprednisolone treatment, how specific question may require appropriate methods, thus emphasizing the non-uniqueness of the approaches. Finally, we explore novel ways for integrating -omics information with PKPD models, towards the development of more integrated pharmacology models.